Learning from Mumbai : practising architecture in urban India - Poiesz, Pelle; Scholte, Gert Jan; Gandhi, Sanne Vanderkaaij (Ahmedabad : Mapin Publishing, 2013)
This book is providing an insight into the making of contemporary architecture and planning in a vibrant mega city. Opening with the reflections of Indian architects Rohan Varma, Charles Correa and Rahul Mehrotra on the past, present and future of architecture and planning in Mumbai, the book continues with interviews with a wide variety of local and foreign architects and planners who work in Mumbai.
Interviews and contributed articles.
Keywords: Urban planning; Architecture -- Urban India -- Mumbai